2021
DOI: 10.1111/jhn.12929
|View full text |Cite
|
Sign up to set email alerts
|

Putting quality food on the tray: Factors associated with patients’ perceptions of the hospital food experience

Abstract: Iatrogenic malnutrition is common among hospital patients and is partially a result of food and beverage intake that fails to meet patients' physiological needs. [1][2][3][4][5][6][7] Hospital malnutrition varies depending on the patient population, tools used for assessment and the timing of assessment, but is estimated to occur in as many as 70% of patients. 2,4,[8][9][10] Malnutrition increases the risk of further morbidity and mortality, 5,8,[11][12][13] and can result in increased hospital costs because o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…A review of the literature (Table 1) and a pretest of the domains examined (Web Appendix Table WC2) reveal that previous investigations that found a positive relationship between company size and quality were conducted in relatively high-tech domains (e.g., hospitals, cars, medical devices, and airlines; Boscarino 1988; Chaudhuri et al 2018; Paharia, Avery, and Keinan 2014). By contrast, investigations that found the opposite result were conducted in relatively low-tech domains (e.g., food services; Morgan 1993; Trinca, Duizer, and Keller 2022). Our conceptual model and empirics offer one explanation for why a larger company size leads to more favorable evaluations for high-tech products but less favorable evaluations for low-tech products.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A review of the literature (Table 1) and a pretest of the domains examined (Web Appendix Table WC2) reveal that previous investigations that found a positive relationship between company size and quality were conducted in relatively high-tech domains (e.g., hospitals, cars, medical devices, and airlines; Boscarino 1988; Chaudhuri et al 2018; Paharia, Avery, and Keinan 2014). By contrast, investigations that found the opposite result were conducted in relatively low-tech domains (e.g., food services; Morgan 1993; Trinca, Duizer, and Keller 2022). Our conceptual model and empirics offer one explanation for why a larger company size leads to more favorable evaluations for high-tech products but less favorable evaluations for low-tech products.…”
Section: Discussionmentioning
confidence: 96%
“…To date, there is no clear consensus in the literature (Table 1). A larger size positively predicts quality evaluations in some cases (e.g., Morgan 1993;Trinca, Duizer, and Keller 2022), but at other times, the relationship reverses (e.g., Boscarino 1988;Chaudhuri et al 2018;Paharia, Avery, and Keinan 2014). We investigated the practical relevance of this question by surveying marketing -✓ -In a correlational design, larger management consultancies are perceived as offering higher-quality services.…”
mentioning
confidence: 99%
“…In a study of 16 hospitals, the most important attributes to patients were found to be taste, freshness, if the food meets dietary needs, right temperature, sufficient amount, and easy to eat (Trinca et al 2021). Patients who eat less than 50% of offered food in their first week in hospital are more likely to deteriorate and stay in the hospital longer due to the dislike of foods or reduced intake due to illness (Allard et al 2015).…”
Section: Unintended Consequences Of Avoiding Highly Processed Foodsmentioning
confidence: 99%
“…The Hospital Food Experience Questionnaire was used to investigate patients' views and perceptions of what they ate in hospital and the patients' priorities included taste, freshness and the availability of appropriate food to meet specific dietary requirements. 1 Surprisingly, the sensory components of meals were seen as less important. 1 Evaluating what patients eat has also been tackled indirectly from hospital food waste audits.…”
mentioning
confidence: 99%
“…1 Surprisingly, the sensory components of meals were seen as less important. 1 Evaluating what patients eat has also been tackled indirectly from hospital food waste audits. From a review of the literature, a food waste audit consensus tool has been developed.…”
mentioning
confidence: 99%